Ta’tsiru Namudaj Al-Ta’allum Al-Qaaim ‘Ala Al-Musykilaat (PBL) Li Qudrati Fahmi Al-Qawaid Al-Lughowiyyah - Huwaiza, Sivani Indan; Inayah; Susanti, Siti Sri; Ismail (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Language proficiency (LP) is an important aspect of mastering good and correct language. However, many students face difficulties in understanding and applying it effectively. This is often due to learning curricula that lack context and active student participation. Students work collaboratively to identify, analyze, and find solutions to complex problems relevant to their lives. This study employs a quantitative research approach with experimental research methods. The study population in this study was seventh-grade students, with a total of 52 students, while the sample was taken from seventh-grade A, with a total of 25 students, using a simple random sampling method. The data analysis method is in the form of statistical analysis and analysis of pre- and post-test results using SPSS 27 and Microsoft Excel, including the correct-test, the fixed-test, the standard-test, and the Wilcoxon-test. The results of this study on the Wilcoxon test showed that the sig 0.000 value was less than 0.05, which means that there is a difference between the pre-test and post-test results, so it can be said that there is a positive effect of PBL between the pre-test and post-test results of seventh-grade students at Fatahillah Islamic Middle School in Semarang in understanding the subject and predicate. The implementation of PBL in ALL can increase students' motivation, critical thinking skills, and language proficiency. This method encourages active student participation, so that they understand the material better and can apply it in a real-life context.